Sex discordance between cell‐free fetal DNA and mid‐trimester ultrasound: a modern conundrum. (28th October 2019) - Ayala, N.K.; Kole, M.B.; Forcier, M.; Halliday, J.; Russo, M.L.
Abstract : What's already known about this topic? Sex discordance between cell‐free DNA and the mid‐trimester ultrasound requires a thorough, systematic workup This allows for earlier recognition and diagnosis of disorders of sex development What does this study add? Recognition in‐utero allows for multi‐disciplinary care and education of families prior to delivery Inclusive language acknowledging the diversity of gender and sexuality is important for provision of equitable, patient‐centered care